2018
DOI: 10.1186/s12890-018-0576-x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of nasal highflow in hypercapnic COPD patients is flow and leakage dependent

Abstract: BackgroundNasal Highflow (NHF) delivers a humidified and heated airflow via nasal prongs. Current data provide evidence for efficacy of NHF in patients with hypoxemic respiratory failure. Preliminary data suggest that NHF may decrease hypercapnia in hypercapnic respiratory failure. The aim of this study was to evaluate the mechanism of NHF mediated PCO2 reduction in patients with chronic obstructive pulmonary disease (COPD).MethodsIn 36 hypercapnic COPD patients (PCO2 > 45 mmHg), hypercapnia was evaluated by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 22 publications
(34 reference statements)
3
52
1
2
Order By: Relevance
“…However, we believe that the main reason is that HFNC effectiveness is flow-and leakage-dependent. at we found no CO 2 reduction in asthmatic patients may be explained by findings reported by Braunlich et al in COPD patients [31]. e latter study demonstrated that effective PCO 2 reduction by HFNC therapy does not correlate with mean airway pressure increase, but with elevated leakage and airflow.…”
Section: Discussioncontrasting
confidence: 57%
“…However, we believe that the main reason is that HFNC effectiveness is flow-and leakage-dependent. at we found no CO 2 reduction in asthmatic patients may be explained by findings reported by Braunlich et al in COPD patients [31]. e latter study demonstrated that effective PCO 2 reduction by HFNC therapy does not correlate with mean airway pressure increase, but with elevated leakage and airflow.…”
Section: Discussioncontrasting
confidence: 57%
“…Thus, the role of HFNC in weaning COPD with hypercapnia is still unclear. Physiological studies reported that the high velocity of the gas could rinse the dead space of the upper airway and reduce carbon dioxide rebreathing (Biselli et al, 2018), to improve alveolar ventilation in COPD, which ultimately improves dyspnea and arterial blood gases (ABGs; Braunlich, Mauersberger, & Wirtz, 2018;McKinstry et al, 2018;Pisani et al, 2017). In the retrospective comparison of HFNC to NIV in postextubation patients by Yoo et al (2016), a subgroup analysis of partial pressure of PaCO 2 >45 mmHg patients showed that reintubation rate and ICU mortality did not differ significantly.…”
mentioning
confidence: 99%
“…Surprisingly, pCO 2 reduced to normal values, despite a decrease in minute volume suggesting it was most likely achieved by washout of the respiratory tract and functional reduction in dead space . In another physiological study of 36 stable COPD patients, the washout effect was correlated with increased leakage and airflow . A randomized cross‐over study (long‐term oxygen therapy versus HFOT at 30 L/min with room air) confirmed that HFOT reduced CO 2 rebreathing, and also showed that it increased tidal volume and improved breathing pattern with a reduction of respiratory rate without any change in minute ventilation .…”
Section: Niv As First‐line Treatment For Acute Respiratory Acidosis Dmentioning
confidence: 92%
“…Ventilatory support is the main physiological effect expected from treatment during a COPD exacerbation. HFOT contributes to reduced respiratory efforts by the PEEP effect and by the reduction of functional dead space through washout in the upper airways contributing to partial pressure of CO 2 (pCO 2 ) reduction . Increased tidal volume and decreased respiratory rate are other physiological effects of HFOT favouring a reduction in the work of breathing in acute hypercapnic respiratory failure …”
Section: Niv As First‐line Treatment For Acute Respiratory Acidosis Dmentioning
confidence: 99%